2007
DOI: 10.1128/aac.00503-07
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa May Accumulate Drug Resistance Mechanisms without Losing Its Ability To Cause Bloodstream Infections

Abstract: In this study, we systematically investigated the resistance mechanisms to ␤-lactams, aminoglycosides, and fluoroquinolones of 120 bacteremic strains of Pseudomonas aeruginosa. Pulsed-field gel electrophoresis genotyping showed that 97 of these strains were represented by a single isolate, 10 by 2 and 1 by 3 clonally related isolates, respectively. Seventy-five percent (90 out of 120) of the bacteremic P. aeruginosa strains displayed a significant resistance to one or more of the tested antimicrobials (up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 35 publications
4
73
0
2
Order By: Relevance
“…In a related analysis, Cabot et al (26) found that oprD mutations underlay the acquisition of high-risk infections due to extensively drugresistant P. aeruginosa infections. In addition, a recent study analyzing different mechanisms of antibiotic resistance that occur in clinical isolates of P. aeruginosa causing severe bloodstream infections concluded that acquisition of resistance did not lead to decreased fitness (27). Consistent with the observations reported here that mutations in the oprD gene in P. aeruginosa can increase fitness for infection, other studies have reported that oprD-inactivating mutations can arise in the absence of carbapenem treatment (28), suggestive of a survival benefit conferred by OprD loss.…”
Section: Resultssupporting
confidence: 78%
“…In a related analysis, Cabot et al (26) found that oprD mutations underlay the acquisition of high-risk infections due to extensively drugresistant P. aeruginosa infections. In addition, a recent study analyzing different mechanisms of antibiotic resistance that occur in clinical isolates of P. aeruginosa causing severe bloodstream infections concluded that acquisition of resistance did not lead to decreased fitness (27). Consistent with the observations reported here that mutations in the oprD gene in P. aeruginosa can increase fitness for infection, other studies have reported that oprD-inactivating mutations can arise in the absence of carbapenem treatment (28), suggestive of a survival benefit conferred by OprD loss.…”
Section: Resultssupporting
confidence: 78%
“…Sekiguchi et al, 2007;Samuelsen et al, 2010), while others pointed out that upregulation of the MexXY efflux system and acquisition of AMEs co-existed in the same clinical P. aeruginosa strains (e.g. Henrichfreise et al, 2007;Hocquet et al, 2007). In this study, we demonstrated that interplay between the MexXY efflux pump and the AAC modifying enzyme in P. aeruginosa provides high-level aminoglycoside resistance in clinical use.…”
Section: Discussionmentioning
confidence: 76%
“…Aminoglycoside resistance in P. aeruginosa has often arisen via acquired aminoglycoside-modifying enzymes (AMEs) and 16S rRNA methylases (RMTs), typically involving the MexXY endogenous efflux system (Poole, 2011). In particular, upregulation of the MexXY efflux pump is common, and MexXY has been implicated in aminoglycoside resistance in clinical isolates, particularly CF isolates (Sobel et al, 2003;Vogne et al, 2004;Henrichfreise et al, 2007;Islam et al, 2004;Hocquet et al, 2007;Vettoretti et al, 2009). A significant relationship between antibiotic use, for example, aminoglycoside, fluoroquinolone and cefepime, and the incidence of MexXY-overproducing P. aeruginosa has been reported (Hocquet et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is also commonly believed that in MDR P. aeruginosa isolates, reduced virulence may result due to decreased biofilm. However, recent data suggest otherwise, and MDR P. aeruginosa may remain fully pathogenic [18].…”
Section: Introductionmentioning
confidence: 99%